POTENSI BIJI LABU KUNING SEBAGAI AGEN FITOESTROGEN PADA WANITA POST MENSTRUAL - Lestari, Beni; Hanif, Naisbitt Iman; Anggarany, Ariska Deffy; Ziyad, Thoriq; Walidah, Ziana; Murwanti, Retno (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Osteoporosis and hypercholesterolemia are prevalent condition in menopausal women. The common therapy to prevent the estrogen degrading condition is Hormone Replacement Therapy (HRT). However, HRT possessed various risks. Curcubita pepo L. seed (pumpkin seed) contains lignan secoisolariciresinol and lariciresinol which exhibit estrogenic effect. The aim of this study is to determine the estrogenic effect of Ethanolic Extract of Pumpkin Seeds (EEPS) through in silico and in vivo study. In silico study were conducted by molecular docking of lignan which is secoisolariciresinol and lariciresinol with Estrogen Receptor (ERÎ± and ErÎ²). In vivo study conducted by using ovariectomized Sprague dawley female rats as a model of postmenopausal women. Blood lipid profile, bone density, and uterine weight were assayed after thirty days. Molecular docking score of secoisolariciresinol and lariciresinol were similar to estradiol. In vivo study found that EEPS increase bone density and uterine weight percentage while also improve the blood profile. In conclusion, these result showed that EEPS is potential to be developed as an osteoporosis and hypercholesterolemia prevention agent.Â Keywords: Â Lime peel, Limonene, Aromatic candles, Repellent